The Contribution of Muslim-Buddhist Relation on Islamic Civilization - Ahmad Faizuddin Ramli; Jaffary Awang; Zaizul Ab Rahman (Universiti Sains Islam Malaysia, 2024)
Vol. 22 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)